2014
DOI: 10.1158/1535-7163.mct-13-0367
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Insulin-like Growth Factor–Binding Protein-3 Signaling through Sphingosine Kinase-1 Sensitizes Triple-Negative Breast Cancer Cells to EGF Receptor Blockade

Abstract: The type I EGF receptor (EGFR or ErbB1) and insulin-like growth factor-binding protein-3 (IGFBP-3) are highly expressed in triple-negative breast cancer (TNBC), a particularly aggressive disease that cannot be treated with conventional therapies targeting the estrogen or progesterone receptors (ER and PR), or HER2. We have shown previously in normal breast epithelial cells that IGFBP-3 potentiates growth-stimulatory signaling transduced by EGFR, and this is mediated by the sphingosine kinase-1 (SphK1)/sphingos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 49 publications
2
65
0
2
Order By: Relevance
“…Additionally, Martin et al (39) demonstrated that IGFBP-3 enhanced EGF signaling and its proliferative effects via increased EGFR phosphorylation and the activation of MAP kinase signaling pathways in breast cancer cells in vitro. An associated previous study also reported that IGFBP-3 promotes the proliferation of breast cancer cells through increasing EGFR signaling mediated by SphK1 (40). Therefore, IGFBP-3 has been suggested to promote angiogenesis by inducing VEGF, thereby inducing EGFR signaling mediated by SphK1 and activation of MAP kinase signaling pathways.…”
Section: Univariate Analysismentioning
confidence: 81%
“…Additionally, Martin et al (39) demonstrated that IGFBP-3 enhanced EGF signaling and its proliferative effects via increased EGFR phosphorylation and the activation of MAP kinase signaling pathways in breast cancer cells in vitro. An associated previous study also reported that IGFBP-3 promotes the proliferation of breast cancer cells through increasing EGFR signaling mediated by SphK1 (40). Therefore, IGFBP-3 has been suggested to promote angiogenesis by inducing VEGF, thereby inducing EGFR signaling mediated by SphK1 and activation of MAP kinase signaling pathways.…”
Section: Univariate Analysismentioning
confidence: 81%
“…We found that treatment mice bearing syngeneic breast tumors with the specific SphK1 inhibitor SK1-I not only suppressed S1P levels in the tumor and circulation, but importantly reduced tumor burden and metastases to lymph nodes and lungs (Nagahashi et al, 2012). Growth of MDA-MB-468 xenograft tumors in mice was significantly inhibited by the SphK1/2 inhibitor SKI-II and the tyrosine kinase inhibitor gefitinib when used in combination, but not as single agents (Martin et al, 2014). Although inhibition of SphK2 has also been reported to reduce tumorigenesis (Antoon et al, 2011b;Liu et al, 2013), further studies are needed to insure that these effects are solely dependent on inhibition of SphK2 activity.…”
Section: Inhibition Of the Er/s1p Axismentioning
confidence: 92%
“…IGFBP-3 was positively correlated with BMI (51) and TNBC was found to be associated with high expression of epidermal growth factor receptor (EGFR) and IGFBP-3 (52,53). IGFBP-3 contributes to the growth of TNBC cells by increasing SphK1-mediated EGFR signaling (54).…”
Section: Insulin Resistance Insulin-like Growth Factor 1 (Igf-1) Andmentioning
confidence: 99%